Face Shape Variation Among Sundanese People from Western Java, Indonesia - WOLLY CANDRAMILA; SONY HERU SUMARSONO; BAMBANG SURYOBROTO; MAELITA RAMDANI MOEIS (Bogor Agricultural University, Indonesia, 2015)
The face is an important visual stimulus in daily life and each face identifies a particular person. The bone structure of the skull along with various soft tissues and coloration influence perception of the face. Facial averageness, and bilateral symmetry are the two most commonly used criterion of facial attractiveness, yet, both may be perceived differently based on hormonal status of the person observed. Facial perceptions may also differ according to cultural norms. In this research, we examined variations in face-shape among Sundanese male and female adults aged 18 to 40. We applied geometric-morphometric methods to analyze the landmark-based morphological variations in the frontal and lateral views of subjects’ faces. We identified five types of female frontal face views and four of male. We also identified five types each of female and male lateral face views. The trichion, gonion and gnathion were three most variable landmarks among the face views in our study, and highly determined the shape of the individuals’ faces. Multiple face type variation may refer to many categories of attractive faces since there is no exactly perfect category in the assessment of facial attractiveness by the viewers. Therefore, we believe that the configuration of facial features cannot constitute the sole visual criterion of facial attractiveness.